MAKNA SIMBOLIK UPACARA TABUIK DI KOTA PARIAMAN SUMATRA BARAT - Vina Dwiyanti; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In Indonesia, many tribal areas that have a habit of ceremonies . At any rate the region has a traditional ceremony has the intent and purpose and its own characteristics which actually can not be separated from the element of history . Traditional ceremony in West Sumatra is famous legendary is Tabuik ceremony held in the city of Pariaman which routinely performed each entered the month of Muharram in the Islamic calendar developed by Shi'ite to Pariaman . Tabuik ceremony is a symbolic form of expression of deep sorrow and respect for Muslims in Pariaman to the Prophet Muhammad's grandson . Pariaman community predominately Minangkabau ethnic group which generally makes the religion of Islam as a religion . Historically , Tabuik ceremony is closely related to the growth and development of Islam . At this time kenyataannyan , Tabuik ceremony in West Sumatra Pariaman city has undergone many shifts in Part of the ritual , and now only be implemented as an object of tourism to attract tourists to the city of Pariaman . The aim of this study was to see how the symbolic meaning Tabuik ceremony in Pariaman city of West Sumatra . This study used a qualitative research method with descriptive approach . The object of this study is the symbolic meaning Tabuik ceremony in Pariaman city of West Sumatra , with a research subject that is all informants that meet the needs of the research consisted of 10 members, namely tuo Tabuik pasa and Subarang , children Tabuik , Head Disbudpar Pariaman city , village children and chairman PKDP Riau through purposive technique . Data collection techniques in this study using in-depth observation and interviews and documentation . Results from this study is that the symbolic meaning Tabuik ceremony can be studied through two aspects: social and physical . The social aspect is the process of making Tabuik which consists of making deraga , taking land , cutting down banana trees, events maatam , mearak fingers , Maarak saroban , tabuik promoted , tabuik hoyak party , and tabuik thrown into the sea . The physical aspects are parts Tabuik consisting of peaks Tabuik , gomaik , top rank , and rank Bouraq below . The shift in meaning to the ceremony ceremony Tabuik influenced by maketh Tabuik be fixed event dijadikannnya Tabuik Pariaman to become the object of western Sumatra tourism . There is a difference between past and present Tabuik , Tabuik ceremony is now aiming for the entertainment and performing arts attractions with the aim to attract domestic and foreign tourists to come and see the show tabuik ceremony and can boost the regional economy and promoting particular areas of West Sumatra Pariaman area .Keyword: symbolic meaning, Tabuik ceremony, symbolic interaction.